Pengaruh Brand Experience, E-Service Quality Dan Promotion Terhadap Keputusan Penggunaan Aplikasi Streaming Musik Joox (Studi Kasus SMA Swasta Panti Harapan Lawe Desky Kec. Babul Makmur Kabupaten Aceh Tenggara) - Arta, Miduk; Trg, Eka Dewi Setia; Amelia, Wan Rizka (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to determine the influence of Brand Experience, E-Service Quality, and Promotion on Decisions to Use the Joox music streaming application (case study SMA Swasta Panti Harapan Lawe Desky Kec. Babul Makmur Kabupaten Aceh Tenggara). The type of research used in this research is explanatory. This explanatory research tests a hypothesis between one variable and another variable which mutually influence each other. The population in this study is cases SMA Swasta panti harapan lawe desky kec. Babul Makmur kabupaten Aceh Tenggara as many as 500 students. The sampling technique uses a purposive sampling method. After carrying out the above method, the sample obtained in this study was 84 students. The test results show that it can be concluded that Brand Experience has a positive and significant effect on Usage Decisions. E-Service Quality has no influence on Usage Decisions. And promotion has a positive and significant effect on usage decisions SMA Swasta Panti Harapan Lawe Desky kec. Babul Makmur kabupaten Aceh Tenggara.